1992
DOI: 10.1002/1520-6629(199210)20:4<353::aid-jcop2290200409>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Is happiness a home in the suburbs?: The influence of urban versus suburban neighborhoods on psychological health

Abstract: Classic urban theory suggests that living in highly urbanized areas of the city results in social isolation, social disorganization, and psychological problems. Living in the suburbs, however, is thought to be much more conducive to happiness, because suburban areas have a lower population density, lower crime, and a more stable population when compared to urban areas. Using data collected in 1974 from the Detroit Metropolitan Area, this study evaluates this “happy suburbanite” hypothesis. Results show that pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
144
2
15

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(170 citation statements)
references
References 41 publications
(56 reference statements)
9
144
2
15
Order By: Relevance
“…From the perspective of energy use and carbon emissions, there is generally support for higher density urban living [2][3][4][5][6][7][8][9][10]. At the same time, from a social perspective, there has been a long-standing argument that people living in dense urban cities may have a lower quality of life (QoL) and are less happy or less satisfied with their lives than those living in the suburbs, based on city and regional data sets [11][12][13][14][15][16][17]. QoL has been widely considered to be an important indicator for social sustainability [18][19][20][21][22][23][24][25][26], and is a multidimensional concept that has been assessed and quantified using a number of objective and subjective indicators across various research communities.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of energy use and carbon emissions, there is generally support for higher density urban living [2][3][4][5][6][7][8][9][10]. At the same time, from a social perspective, there has been a long-standing argument that people living in dense urban cities may have a lower quality of life (QoL) and are less happy or less satisfied with their lives than those living in the suburbs, based on city and regional data sets [11][12][13][14][15][16][17]. QoL has been widely considered to be an important indicator for social sustainability [18][19][20][21][22][23][24][25][26], and is a multidimensional concept that has been assessed and quantified using a number of objective and subjective indicators across various research communities.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that longer residence means greater neighbourhood satisfaction (Adams, 1992;Marans and Rodgers, 1975), while in others the length of residence has been associated with a lower level of neighbourhood satisfaction (Lu, 1999;Dekker et al, 2007;Parkes et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the urban quality of life is recognized as a relevant component of an individual's general quality of life. Many studies have found that satisfaction with urban living environments contributes significantly to overall life satisfaction (Sirgy and Cornwell, 2001;McCrea et al, 2005;Horelli, 2006;Power et al, 1999;Adams, 1992). This paper analyses the quality of life in chosen neighbourhoods in the city of Rijeka.…”
Section: Introductionmentioning
confidence: 99%
“…En tal sentido, se ha analizado la forma en que las condiciones físicas, sociales y económicas de la colonia influyen en la satisfacción con ésta, lo que a su vez determina el nivel de satisfacción con la vida (Salleh y Badarulzaman, 2012;Miller et al, 1980); también ha sido importante determinar cómo el grado de satisfacción es un factor que influye en las decisiones de mudarse de los residentes (Clark et al, 2006;Brower, 2003;Droettboom et al, 1971;Kasl y Harburg, 1972;Lee et al, 1994;Nathanson et al, 1976;Newman y Duncan, 1979;Quigley y Weinberg, 1977); en el nivel o calidad de vida (Campbell et al, 1976;Sirgy et al, 2000;McCrea et al, 2005;Sirgy y Cornwell, 2002;Parkes et al, 2002), así como en la educación que reciben los hijos en el hogar (Martinez et al, 2002). Se ha reconocido que los residentes que experimentan mayor satisfacción con su colonia reportan mejor salud mental, perciben menos inseguridad y muestran una menor probabilidad de mudarse (Baba y Austin, 1989;Adams, 1992;Bolan, 1997;Sirgy y Cornwell, 2002;Austin et al, 2002;Oh, 2003).…”
Section: Literatura En Torno a La Satisfacción Con La Coloniaunclassified